Early and Delayed Alteration of Atrial Electrograms Around Single Radiofrequency Ablation Lesion - Havranek, Stepan; Alfredova, Hana; Fingrova, Zdenka; Souckova, Lucie; Wichterle, Dan (Frontiers in Cardiovascular Medicine, 2019)
Purpose: The acute effect of radiofrequency (RF) ablation includes local necrosis and oedema. We investigated the spatiotemporal change of atrial electrograms in the area surrounding the site of single standardized pulse of RF energy. Methods: The study enrolled 12 patients (45–67 years, 10 males) with paroxysmal atrial fibrillation (AF) undergoing ablation procedure with irrigated-tip ablation catheter and 3D navigation. The high-density mapping/remapping (129 ± 63 points) within the circular area with radius of 10 mm, centered at the pre-specified posterior left pulmonary vein antrum ablation site was performed at baseline, immediately after single RF energy delivery (25 W, 30 s, 20 ml/min) and after 30 min waiting period. Bipolar voltages of atrial electrograms (A-EGM-biV) were averaged within the central and 12 adjacent left atrium segments and their relative change was studied. Results: After the ablation, overall A-EGM-biV within the mapping zone (3.51 ± 1.89 mV at baseline) reduced to 2.83 ± 1.77 mV (immediately) and to 2.68 ± 1.58 mV (after 30 min waiting period). In per-segment pair-wise comparison, we observed highly significant change in A-EGM-biV that extended up to the distance of 8.8 mm from the lesion core. The maximum early A-EGM-biV attenuation by 39–49% (P < 0.001) was registered in segments adjacent to pulmonary vein ostia. The subsequent (delayed) A-EGM-biV reduction by 17–24% (P < 0.05) was observed in opposite direction from the lesion center. Conclusions: Significant alteration of atrial electrograms was detectable rather distant from the central lesion. Spatiotemporal development of ablation lesion was eccentric/asymmetric. While acute A-EGM-biV reduction can be attributed predominantly to direct thermal injury, delayed effects are probably due to oedema progression.